2016
DOI: 10.1111/ppa.12629
|View full text |Cite
|
Sign up to set email alerts
|

Fungal derived cytokinins are necessary for normal Ustilago maydis infection of maize

Abstract: Phytohormones derived from fungi play a key role in regulating plant-pathogen interactions; however, deciphering the separate contributions of pathogen and plant during infection has been difficult. Here, the Ustilago maydis-Zea mays pathosystem was used to investigate this chemical exchange. Ustilago maydis, the causative agent of maize smut, produces cytokinins (CK), which are a group of phytohormones responsible for directing plant development. The characteristic symptom of smut disease is the formation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
68
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(72 citation statements)
references
References 40 publications
4
68
0
Order By: Relevance
“…By using mass spectrometry, this study reports the presence of several additional mammalian CK types beyond the ones published to date, and documents the fate of iP‐ and 2MeS‐type CK production in HeLa cell culture. Moreover, this study reveals the interconversion of iP‐type CKs consistent with findings in plants, fungi, and other CK‐producing organisms . Similarly, we demonstrate that HeLa cells are able to take up and metabolize an exogenously applied CK, BAR, converting it into different structural derivatives.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…By using mass spectrometry, this study reports the presence of several additional mammalian CK types beyond the ones published to date, and documents the fate of iP‐ and 2MeS‐type CK production in HeLa cell culture. Moreover, this study reveals the interconversion of iP‐type CKs consistent with findings in plants, fungi, and other CK‐producing organisms . Similarly, we demonstrate that HeLa cells are able to take up and metabolize an exogenously applied CK, BAR, converting it into different structural derivatives.…”
Section: Discussionsupporting
confidence: 88%
“…Moreover, this study reveals the interconversion of iP-type CKs consistent with findings in plants, fungi, and other CK-producing organisms. 4,16,38 Similarly, we demonstrate that HeLa cells are able to take up and metabolize an exogenously applied CK, BAR, converting it into different structural derivatives.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…On the other hand, no active FB fraction and no cZ form CKs 245 were detected in cedar control twigs. In a similar manner, infected apple tissue comprised of 246 pycnia on the upper (adaxial) and aecia on the lower (abaxial) leaf surface where the aeciospore 247 production occurs, had much different hormone profiles than the non-infected control leaves.D r a f t development suggests that the fungus is excreting hormones using the common or modified 250 mevalonate (MVA) pathway, similar to the one described for U. maydis, a fungus infecting corn 251 (Morrison et al 2015a(Morrison et al , 2017 and consistent with the signature CK pathway reported from a 252 large survey of fungal species (Morrison et al 2015b). On the contrary, in the non-infected 253 control cedar twigs and apple leaves the plant methylerythritol phosphate (MEP) pathway was 254…”
Section: Discussion 232mentioning
confidence: 57%